PENGARUH PENATAUSAHAAN ASET TETAP DAN PENERAPAN SISTEM INFORMASI MANAJEMEN AKUNTANSI BARANG MILIK NEGARA (SIMAK-BMN) TERHADAP KUALITAS LAPORAN KEUANGAN PADA KANTOR PERTANAHAN KOTA BANDUNG - Dady Nurpadi; Mila Hermawati (Program Studi Akuntansi IKOPIN, 2021)
Effect of Fixed Asset Administration and Implementation State PropertyAccounting Management Information System (SIMAK-BMN). Against theQuality of Financial Statements at the National Land Agency Bandung DistrictOffice. Under the guidance of Ir. H. Dady Nurpadi, MP and M. Ardi NupiHasyim., SE., M.AB. This study aims to determine the implementation of fixedassets management and Implementation of SIMAK-BMN and Its Effect onReport Quality Finance at the National Land Agency Bandung District Office.This research uses a quantitative method with an associative approaching.Sample detemenation is using saturated sampling, the sample in this study isfinancial division and BMN Bandung City Land Office as many as 10 people The data analysis used is multiple regression analysis.The results showed that partially Administration variables Fixed assets have apositive effect on the quality of financial statements, and implementationSIMAK-BMN has a positive effect on the quality of financial reports. InSimultaneously, the Administration variable and SIMAK-BMN implementationhad a positive effect on Quality of Financial Statements of National LandAgency Bandung District Office. This matter indicates that the National LandAgency Bandung District Office has implemented Management Fixed Asset andSIMAK-BMN Implementation